The Virgin and Child with Angels. - Stone, George Eathl (photographer):::Creator::::::::::::
The image depicts the Madonna Enthroned, from the Church of Ognissanti, Florence, ca. 1310. Tempera and gold leaf on wood, 10′ 8″ X 6′ 8″. Galleria degli Uffizi, Florence (1266? - 1337).